A relay of anticyclonic eddies transferring North Pacific subtropical mode water into the South China Sea - Wang, Ran; Ren, Qiang; Nan, Feng; Yu, Fei (Frontiers in Marine Science, 2023)
North Pacific subtropical mode waters (STMWs), which are subducted with air-sea interaction signals and characterized by low potential vorticity (PV), play an important role in climate change issues. STMW (PV<2×10^(-10) m^(-1)∙ s^(-1)) can be advected westward by large-scale ocean circulation and mesoscale eddies. However, whether and how the STMW intrudes into the South China Sea (SCS) remains unclear. Low PV signals that originate from the STMW and intruding into the SCS are investigated by comparing observations and ocean general circulation models during 2003-2017. These signals mostly move across the Luzon Strait (LS) into the SCS during the 2008-2009 and 2014-2016 periods. The results of case studies selected from these two periods indicate that the low PV signals can move to the LS and are trapped by anticyclonic eddies (AEs). When the velocity vorticity is negative southwest of Taiwan Island, vertical stratification becomes weaker west of the coming AE (AE1), and low PV signals can consequently be transported along the STMW layer (25.0 σ_θ - 25.5 σ_θ isopycnal layer). Thus, an AE (AE2) forms east of AE1 and isolates the low PV signal from AE1, and then AE2 transports the low PV water southwestward in the SCS. In contrast, the low PV signal has difficulty migrating eastward when the velocity vorticity is positive west of AE1, as vertical stratification strengthens and then weakens that signal. The results suggest that only AEs can relay low PV signals from east of the LS and carry them over long distances in the SCS.